"The Dragon Can't Roar": Analysis of British Expatriate Masculinity in Yusuf Dawood's One Life Too Many. (1st September 2020) - Mate, Antony Mukasa
Abstract: This article examines British masculinity in Kenya. It focuses on British expatriate Sydney Walker, the protagonist of Yusuf Dawood's One Life Too Many, who moves to Kenya at the height of British colonial rule and stays on in the new postcolonial state under black rule. It looks at how he constructs his masculinity among fellow men and in relation to the female other. Walker struggles to retain the colonial masculinity of his predecessors amid shifting terrain. Using the key concepts of hegemonic and subordinate masculinities as presented in Raewyn Connell's masculinity theory, which argues that gendered relationships in institutions are controlled by power, this article examines the diverse masculinities in One Life Too Many and argues that sex plays a major role as an instrument of power that heterosexual men use to dominate other men and subordinate women. It contends that the power dynamics in the sexual arena symbolically represent the shifting power relations in the postcolonial Kenyan state, in which the status of British working-class men had changed due to their loss of political power.